Development of ICT-Based Mathematical Learning Media on Linear Program Materials to Improve Students Achivement - Puji Karuniakhalida; Maimunah; Atma Murni (Magister Mathematic Education Department Faculty of Teacher Training and Education Universitas Riau, 2019)
This research was inspired by the lack of ICT-based learning media in linear program material. Linear program material has the potential to be developed visually using computer devices to facilitate students in understanding the linear programs. The aim of the study was to develop ICT-based mathematics learning media that met the validity, practicality and effectiveness. The instruments used in this research were material validation sheets, media validation sheets, response questionnaires and student achievement test. Questionnaire sheets were analyzed quantitatively and qualitatively. Based on the results of data analysis and discussion, it can be concluded that the ICT-based media of mathematics learning is valid with an average score of 3.36 by the material validator and 3.42 by the media validator. This learning media also fulfills practical requirements with an average student response of 3.45 in small group trials and 3.18 in large group trials. Learning media also influence students achievement learning. Student achievements in this research are in sufficient criteria that is 65.21%.